The Influence of Utilitarian, Hedonic, and E-Service Quality on Consumer Satisfaction Toward E-Grocery - Yoshua Kolondam; Edwin Reynaldi; Kirana Ariesta Darmawan; Rini Setiowati (International Journal Labs, 2023)
Digitalization has rapidly changed consumer behavior. People can easily buy items from the internet, including groceries, without having to pay for them. Due to this demand, several e-grocery platforms have emerged. High competition in the e-grocery industry is forcing the company to adopt a new marketing strategy. This study examined factors that might affect customer satisfaction with products or services provided by e-groceries. Moreover, the study was conducted to gather a more comprehensive view of online grocery purchasing in Indonesia by combining shopping value and e-service quality that impact customer satisfaction, repurchase intention, and e-WOM purchase and purchase value in Indonesia and the U.S. It shows that shopping value (utilitarian and hedonistic) and e-service quality have a positive impact on customer satisfaction. Moreover, if customer satisfaction is fulfilled, this leads to repurchase intentions and a positive word-of-mouth response to a customer's satisfaction level. A quantitative method was used in this study with the following criteria for respondents: they must live in Jabodetabek and have used e-grocery in the past three months. The data were simulated using the SMART PLS 4 software.